Relief instead of development aid - Gunnar Myrdal (Intereconomics, 1981)
Formerly an active supporter of the western industrialized countries', and particularly Sweden's, policy of development aid, Gunnar Myrdal has in recent years become increasingly critical of the present form of aid. In the following paper the Swedish Nobel Prize winner presents his case for a new line of aid policy.
Keywords: 330; Development Strategy